Bilateral Spontaneous Pneumothorax, Pneumomediastinum, and Subcutaneous Emphysema: Rare and Fatal Complications of Asthma. (23rd December 2012) - Karakaya, Zeynep; Demir, Şerafettin; Sagay, Sönmez Serkan; Karakaya, Olcay; Özdinç, Serife
Abstract : Simultaneous bilateral spontaneous pneumothorax (SBSP) and pneumomediastinum are complications rarely observed synchronously during an acute asthma attack. It is a clinical condition that manifests itself with serious respiratory distress and must be rapidly diagnosed and treated. Although bilateral spontaneous pneumothorax has already been reported in asthma patients in the literature, its concurrence with subcutaneous emphysema and pneumomediastinum is extremely rare except for iatrogenic conditions. By sharing this case about a 39-year-old patient who presented to the emergency room with severe respiratory distress and developed cardiopulmonary arrest during his physical examination, our aim is to emphasize that a rapid diagnosis and treatment by the emergency physicians is the only way for survival in these patients.